Dividend Policy in USA and UK - Zhang, Xiliu (2012)
Dividend policy is always an interesting topic in financial research. One reason is dividend policy affects capital structure of firms when retained earnings intent to fund the firm (AL-Shubiri, 2011). There are also so many arguments and hypotheses about dividend policy. The motivation of this paper is to research about factors that might be significant in determining USA and UK dividend policy. Furthermore, the paper wants to give investors a clear understanding of the difference between UK and USA dividend policy. The data used in this paper all comes from DataStream 5.1 which constituent data of the London Stock Exchange (LSE) of the UK stock market and NASDAQ and New York Stock Exchange (NYSE) of the USA stock market in the period of ten years that from 2001 to 2010. According to the comparison, the dividend payment behaviours of two countries are differently. UK firms always pay higher dividends than USA firms. Dividend pay-outs of UK and USA are affected by different determinants according to the results of fixed effect models. Sales growth is negative correlated with dividend pay-out but leverage is positive correlated with dividend pay-outs in UK. However, just tax is statistically significant for USA firms which positive correlated with dividend pay-outs. Furthermore, regional difference can be found between UK and USA which affects the dividend pay-outs. Miller (1986) claimed that tax is a very important factor that affects dividend pay-out in many countries. The major difference between UK and USA is their tax systems. UK follows an imputation tax system but USA follows a classical tax system. USA firms have a heavy tax burden under classical tax system because double tax should be paid. Simultaneously, dividend payments of firms under imputation tax system are always higher than classical tax system (Alzahrani and Lasfer, 2008) which because USA firms should pay more taxes than UK firms. Hence UK firms have more retained earnings than USA firms. Furthermore, UK firms are encouraged to pay dividends under imputation tax system. Finally, tax reforms also have significant impact on dividend policy. The 2003 dividend tax reforms in USA result in an increase in dividend pay-outs but 1997 ACT reforms in UK reduce dividend pay-outs of firms. Thus, tax actually has significant impact on dividend policy.